Triisobutylaluminium-Mediated Regioselective Protection of Sterically Hindered Amide NH of Cyclo-(AA-Gly): Key Building Block for Next-Generation Peptide Synthesis - Ramakrishna, Isai; Hattori, Tomohiro; Ishiguro, Tomomi; Yamamoto, Hisashi (Synlett, 2023)
In this study, we address the challenge of regioselective Boc protection in the more sterically hindered amide NH of unsymmetrical 2,5-diketopiperazines (DKPs) formed from glycine and various amino acids. Our research introduces a novel technique utilizing cost-effective triisobutylaluminium and trimethoxysilane. Notably, trimethoxysilane selectively reacts with the less hindered amide NH, facilitating the regioselective Boc protection of the more congested amide NH in DKPs. The primary objective of our work is to develop a straightforward and scalable approach for the synthesis of Boc-protected DKPs, with a focus on addressing the steric challenges presented by these compounds. We successfully demonstrate the scalability of this method, enabling the synthesis of a variety of mono-Fmoc-, Cbz-, Alloc-, and EtOCO-protected DKPs. Furthermore, we extend the applicability of this strategy by employing it in the construction of pentapeptides through a twofold peptide-elongation process. Our findings reveal the versatility and efficiency of this regioselective Boc-protection method. Overall, this research introduces a valuable solution to the regioselective Boc-protection challenge in DKPs and demonstrates its applicability in peptide synthesis, showcasing its potential for further advancements in the field.
Keywords: triisobutylaluminium; mono-Boc-DKPs; trimethoxysilane; peptide elongation; regioselective protection